2019
DOI: 10.1002/jcla.22929
|View full text |Cite
|
Sign up to set email alerts
|

Changes in glucose‐lipid metabolism, insulin resistance, and inflammatory factors in patients with autoimmune thyroid disease

Abstract: BackgroundAutoimmune thyroid disease (AITD) is a common organ‐specific autoimmune disorder, and genetic, environmental, and endogenous factors are responsible for initiation of thyroid autoimmunity. Some AITD patients suffer from a certain degree of glucose‐lipid metabolism disorder. This study aims to explore the changes in glucose‐lipid metabolism, insulin resistance, and inflammatory factors in patients with AITD.MethodsA total of 91 patients with Hashimoto's thyroiditis were retrospectively analyzed and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
1
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 23 publications
5
40
1
4
Order By: Relevance
“…However, our study did not show a significant correlation between vitamin D and HT, so it can be seen that vitamin D may be reduced in HT, but lower vitamin D level is not a risk factor for HT, and it cannot cause an increase in its incidence. TSH is considered a potential stimulator of interleukin (IL)-6, IL-12, and tumor necrosis factor (TNF)-α in HT patients (17). Our study found that TSH was higher in the HT group, and according to the literature, TSH further promoted the release of inflammatory factors, suggesting that TSH may be associated with the occurrence of HT.…”
Section: Discussionsupporting
confidence: 66%
“…However, our study did not show a significant correlation between vitamin D and HT, so it can be seen that vitamin D may be reduced in HT, but lower vitamin D level is not a risk factor for HT, and it cannot cause an increase in its incidence. TSH is considered a potential stimulator of interleukin (IL)-6, IL-12, and tumor necrosis factor (TNF)-α in HT patients (17). Our study found that TSH was higher in the HT group, and according to the literature, TSH further promoted the release of inflammatory factors, suggesting that TSH may be associated with the occurrence of HT.…”
Section: Discussionsupporting
confidence: 66%
“…Thyroid autoantibodies were believed to have potential systemic functions ( 16 ). We observed significant decrease in MAFLD prevalence with the rise of serum TRAb and TgAb.…”
Section: Discussionmentioning
confidence: 99%
“…Both innate immunity ( 14 ) and adaptive immunity ( 15 ) contribute to the progression of MAFLD. In autoimmune thyroid diseases (AITD), thyroid autoantibodies not only cause damage to thyroid tissues, but may also have potential out-thyroid actions ( 16 ). Recently, studies have shown that the presence of thyroid antibodies are involved in glucose and lipid metabolic disorders ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…They proved that TNF-α levels were higher for people with hypothyroidism compared to people with levelled thyroid hormones. Interestingly, this concentration showed a decreasing relationship for hypothyroidism and euthyreosis in the group of sick people and among healthy people [17]. Results from as early as the 1990s suggested that TNF-α is present in the thyroid tissue of its various diseases.…”
Section: Discussionmentioning
confidence: 98%